Konsep Perkembangan Peserta Didik dan Hukum-hukum Perkembangan - Habsy, Bakhrudin All; Khairunnisa, Khairunnisa; Jannah, Ilda Miftakhul; Hanifudin, Muhamad (Lembaga Yasin AlSys, 2024)
The development of students' interests and talents as well as character education can be influenced by several factors, namely factors that influence children's development and factors that hinder children's development. There are several laws of individual development, namely the cephalocaudal law, the proximodistal law, the law of developmental rhythm, the law of convergence, the law of recapitulation, the law of survival and self-development, and the law of development tempo. The aim of this research is to determine student development and the laws of development and to make it easier for students to develop their own potential. The method used is qualitative with literature study. Through the results of the literature study, it can be concluded that there are several factors that are very important in supporting the development of students, one of which is the nature and environmental factors that influence the development of each child's personal potential and talent interests. 7 stages of development in humans, there are 3 factors that influence child development proposed by Schopenhauer, John Locke, and Wilian Stern. There are inhibiting factors that influence children's development and the laws of development in children.